(untitled) (Orinoquia, 2022)
This research work analyzes the causes of red bovine viscera seizures in Frigorestrepo Meta, its relationship with the emergency activities carried out and other associated factors during the first year of the pandemic. Frigorestrepo is one of the three regional animal processing plants that is currently endorsed and has permanent inspection by the National Institute of Food and Drug Surveillance (INVIMA) in the department of Meta. The research design is a non-experimental mixed cross-sectional study. Data were obtained from the database of red viscera seizures during the first year of the pandemic and through surveys with responsible actors, both in the slaughter process and with the official inspection activities. The statistical analysis is descriptive, taking as variables (type of viscera, cause of seizure and quantity). The results of the study suggest that the lung is the organ that was seized most often due to emphysema and bronchial aspiration. It is concluded that lung seizures were associated with the desensitization process due to a change of operating personnel due to incapacities generated by Covid-19, as well as to the absence of the head immobilizer of the sensitization equipment/box.